2017
DOI: 10.4103/0971-4065.176146
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of early tacrolimus conversion to sirolimus after kidney transplantation: Long-term results of a prospective randomized study

Abstract: We report a prospective, open-label, randomized study to evaluate the safety and efficacy of converting patients with a stable renal function from tacrolimus (Tac)-based regimen to a sirolimus (SRL)-based regimen after kidney transplantation. Fifty-eight low-risk renal allograft recipients who receiving Tac 6 months posttransplant, were randomly assigned to continue Tac (n = 29) or convert to SRL (n = 29). We evaluated the 3-year outcomes including patient and graft survival, graft function, and safety profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(50 reference statements)
0
5
0
1
Order By: Relevance
“…Calcineurin inhibitor (CNI) minimization or elimination is a critical strategy to decrease CNI toxicities, such as nephrotoxicity, the worsening risk of cardiovascular disease, new-onset diabetes, increased incidence of neoplasms, and viral infections. Some studies have demonstrated well-maintained graft functions without increased rates of graft rejection and failure after CNI elimination using sirolimus in kidney transplantation [37,38]. In addition, the mTOR signaling pathway plays a vital role in tumor initiation and progression.…”
Section: Intact Graft and No Tumor Progression After A Pd-1 Inhibimentioning
confidence: 99%
“…Calcineurin inhibitor (CNI) minimization or elimination is a critical strategy to decrease CNI toxicities, such as nephrotoxicity, the worsening risk of cardiovascular disease, new-onset diabetes, increased incidence of neoplasms, and viral infections. Some studies have demonstrated well-maintained graft functions without increased rates of graft rejection and failure after CNI elimination using sirolimus in kidney transplantation [37,38]. In addition, the mTOR signaling pathway plays a vital role in tumor initiation and progression.…”
Section: Intact Graft and No Tumor Progression After A Pd-1 Inhibimentioning
confidence: 99%
“…According to Liu et al [77]; El-Agroudy et al [85]; Shihab et al [20]; Thomas [10] calcineurin inhibitors (CNIs) used to prevent kidney rejection, may initially protect the renal transplant against immunologic injury but may subsequently cause damage as a result of long-term nephrotoxicity. According to these authors, the low early acute rejection rates achieved using CNIs are not accompanied by improvements in long-term outcomes.…”
Section: Nephrotoxicitymentioning
confidence: 99%
“…Для решения данной задачи многими авторами предлагаются различные стратегии снижения нагрузки ингибиторов кальциневрина в раннем посттрансплантационном периоде. Одной из них является назначение низких доз такролимуса (с достижением целевой концентрации в пределах 3-8 нг/мл) в комбинации с ингибиторами mTOR сразу после трансплантации [10][11][12]. По нашему мнению, включение этих препаратов в иммуносупрессивные схемы отдаленного послеоперационного периода для снижения эффекта нефротоксичности CNI в ряде случаев безусловно оправдано, однако в первые дни после трансплантации использование ингибиторов mTOR может быть связано с повышенным риском раневых инфекционных осложнений.…”
Section: Discussionunclassified